Effect of alpha-linolenic acid on aminoglycoside nephrotoxicity and RhoA/Rho-kinase pathway in kidney - Percin Pazarci; Serkan Özler; Halil Mahir Kaplan (PeerJ)
Aminoglycoside nephrotoxicity stands as a primary contributor to the development of acute intrinsic renal failure. Distinctive characteristic associated with this nephrotoxicity is the occurrence of tubular necrosis, which is why it is commonly referred to as acute tubular necrosis. Studies have demonstrated that inhibiting rhoA/rho-kinase pathway is beneficial for kidney damage induced by diabetes and renal ischemia. Comparable pathological conditions can be observed in aminoglycoside nephrotoxicity, like those found in diabetes and renal ischemia. Gentamicin, an aminoglycoside, is known to activate Rho/Rho-kinase pathway. The primary goal of this study is to explore influence of oxidative stress on this pathway by concurrently administering gentamicin and alpha-linolenic acid (ALA) possessing known antioxidant properties. To achieve this, gentamicin (100 mg kg−1) and ALA (70 mg kg−1) were administered to mice for a period of 9 days, and Rho/Rho-kinase pathway was examined by using ELISA. Administration of gentamicin to mice led to an elevation in RhoA and rho-kinase II levels, along with the activity of rho-kinase in kidneys. However, ALA effectively reversed this heightened response. ALA, known for its antioxidant properties, inhibited activation of Rho/Rho-kinase pathway induced by gentamicin. This finding suggests that gentamicin induces nephrotoxicity through oxidative stress.